Legal Responsibility Of Bpom In Monitoring Illegal Cosmetic Products (Case Study: Salmon Dna Product By Dr. Richard Lee) - Hafizhah, Nur (JURNAL MAHASISWA YUSTISI, 2025)
This study examines the legal liability of the Indonesian Food and Drug Authority (BPOM) in supervising the circulation of illegal cosmetics in Indonesia, focusing on a case study of the Salmon DNA product by Dr. Richard Lee. The background of this research is based on the widespread distribution of illegal cosmetics without marketing authorization, which endangers consumer safety, along with the rising trend of influencer-driven promotions on social media. The objective of this study is to analyze the forms of legal protection provided to consumers and to evaluate the supervisory role of BPOM in addressing such violations. This research employs a normative juridical method with a qualitative approach through literature review, analysis of statutory regulations, legal literature, and BPOM reports. The findings reveal that BPOM possesses sufficient legal instruments and authority to carry out both preventive and repressive supervision; however, its effectiveness is still hindered by limited resources, rapid technological advancements that accelerate the distribution of illegal products, and low consumer awareness. The Salmon DNA case study exposes violations related to the marketing authorization concerning the use of injection methods that do not comply with regulations. The recommendations proposed include the need to enhance public education, strengthen cross-sectoral coordination, and enforce stricter legal measures to minimize consumer risks and reinforce legal protection. This research is expected to contribute valuable input for the development of cosmetic supervision policies in Indonesia.